Supply chain of automotive industry in Bangladesh: feasibility and sustainability with BoP. - Uddin, Md. Rubaiat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.